5 - Digital Publishing and Open Access for Social Science Research Dissemination: A Case Study - Eve Horwitz Gray,; Francois van Schalkwyk,; Karen Bruns, (Africa Media Review, 2007)
This case study charts the planning and implementation of a digital publishing programme over a three-year period at the Human Sciences Research Council, a large South African social science research body. This paper places the case study in the context of research dissemination in South Africa and Africa and reviews new publishing approaches, including electronic publishing and Open Access. It then charts the three phases of the consultancy — investigation, recommen-dations and implementation — and, at each stage, examines successes and failures; the problems encountered; and how they were addressed. It deals with the following challenges faced by African scholarly organisations wanting to use digital media to disseminate their research findings: i. Finding the right strategy, copyright model and business plan for the digital publishing programme; ii. Selling this strategy to the research community and overcoming academic conservatism, entrenched as it often is in traditional ways of publishing; iii. Finding the right mix of technologies (in this case, online content dissemination linked to print-on-demand); iv. Managing the technical and organisational process of getting a digital publishing programme up and running; and v. Ensuring effective promotional and distribution strategies – a matter of overwhelming importance in ensuring the success of a digital publishing programme. The findings of this study will stress the importance of the strategic choices made. In particular, the organisation found that it could use digital media to build the reputation of the organisation. The Open Access copyright model adopted by the organisation allows for the accessibility of primary source information, while at the same time couching and developing the reputation of the organisation. The case study will examine how applicable its findings are to other countries in Africa. In particular, it will explore the limitations of digital dissemination in a South African context and identify the ways in which a multi-pronged approach, using digital, print, e-mail and fax, can most effectively reach a wider market. The conclusion is that this multi-pronged approach can be an effective way of ensuring the international reach of Africa scholarship.